2017
DOI: 10.3390/en10122100
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Surface Borehole Wall Dislocation Induced by Top-Coal Longwall Mining

Abstract: Underground coal extraction causes failure and movement of overlying strata, which could also result in the dislocation of vertical surface boreholes. Investigating the correlation between the dislocation of surface boreholes and the broken of overlying strata is of great significance in deducing the mining-induced dynamic movement of overlying strata, which cannot be seen inside the 'black box'. Field measurement, laboratory experiment and theoretical analysis were employed to study the mechanism of the minin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The subsidence produced by the ground movement is different to the horizontal movement [38,39], so the deformation is characterized by slope, curvature, and horizontal strain. The deformation of the aquitard floor at different mining depths after coal mining ended is shown in Figure 10 It was shown that the subsidence, the slope, the horizontal strain, and the curvature of the clay aquitard floor enlarged as the thickness of the overlying strata decreased.…”
Section: Relationship Between the Deformation Of The Floor Aquitard Amentioning
confidence: 99%
“…The subsidence produced by the ground movement is different to the horizontal movement [38,39], so the deformation is characterized by slope, curvature, and horizontal strain. The deformation of the aquitard floor at different mining depths after coal mining ended is shown in Figure 10 It was shown that the subsidence, the slope, the horizontal strain, and the curvature of the clay aquitard floor enlarged as the thickness of the overlying strata decreased.…”
Section: Relationship Between the Deformation Of The Floor Aquitard Amentioning
confidence: 99%
“…The observation hole was 230 m from the central transport roadway for 2# seam and 95 m from 20104 tailgate, as shown in Figure 1. This hole is about 250 m deep and its mouth at the surface has an elevation of +829.9 m. The positions of key strata in the overburden were identified using KSPB, software for locating key strata (the computational method of this software is based on the key Strata theory and the identification of KS) [25,26]. It was found that there are four key strata above working face 20104, including a PKS and three secondary key strata (SKS) (Figure 3).…”
Section: Field Measurements Of the Height Of Cfzmentioning
confidence: 99%
“…Wen et al [14] found that the key stratum has a significant impact on the behavior of the strata in a stope by theoretical calculation, and divided it into a "single key stratum" structure and a "double key strata" structure. Ju et al [15] adopted in-situ investigation of surface boreholes and found a strong correlation between dislocation inside the boreholes and the location of the key strata, from which the fracture and movement of the key strata with the advancing process of the working face was inverted. Kuang et al [16] carried out an in-situ investigation to determine the law of fracture and movement of a key stratum.…”
Section: Introductionmentioning
confidence: 99%